TOOLS THAT IMPROVE THE LOCAL GOVERNING-BUDGETING WITH PARTICIPATION. THE CASE OF THE MUNICIPALITY OF KAMZA - ALBANIA - Mziu, Xhelal; Xarba, Belinda; Shehu, Hidajet (European Scientific Journal, ESJ, 2012)
Participatory budgeting is an innovation that enables citizens to participate in decision making for management of all or some parts of the active resources of the municipality as the unit of local government. It aims to increase the level of transparency, accountability and social inclusion in local government. Local Government budget is the main document of the municipality, which represents the costs for public services, investment and community priorities. Budgeting decisions define the quantity, quality, cost and services that fit local needs and priorities. Each year, groups representing business, domain experts and citizens are part of the preparation of the fiscal package, so taxpayers are informed about the level of local taxes and fees that will apply the following year and the manner of their use. Experience has shown that participatory budgeting is important as a participatory mechanism, as it contains clear initiatives citizens, local government and local councilors. Moreover, participatory budgeting has produced tangible results, since it relates directly with existing resources rather abstract terms of development plans. Above all, participatory budgeting has built the trust of citizens to local authorities for good governance, increasing transparency, accountability and legitimacy. An innovation in Kamza Municipality in the recent years has been extra budget, which is powered by the good management of municipal funds. Among the main characteristics of participatory budgeting in municipalities is that citizens can participate directly and not need to be represented by an official entity, such as trade unions or NGOs. Clearly, policy and planning is based on facts, allocation of resources according to needs, throwing new ideas, information and resources, risk management through an increased public vigilance, increased confidence in local governance and capacity building and citizenship.